Therapy for Children with Henoch-Schonlein Purpura Nephritis: A Systematic Review - Marco Zaffanello; Milena Brugnara; Massimo Franchini (The Scientific World Journal)
Although severe kidney involvement in children with Henoch-Shonlein purpura (HSP) is rarer than that in adults, morbidity should not be underevaluated and follow-up is mandatory. Some drugs are introduced as well-defined treatment options, others can be promising therapeutic alternatives.